Dangerous Implication of Takfir (Sophist: Jurnal Sosial Politik Kajian Islam dan Tafsir, 2021)
Faith is a fundamental principle in religion. In Islam faith is an initial unitary step in undergoing worship which is called the pillars of faith. They are belief in Allah SWT, angels, scriptures, prophets, afterlife, andin the good and bad conditions which are had by His servants. However, in modernity and the treasures of Islam, Islam seems to be a late religion to be born. By reviving the strong desire in the golden era of the Salaf al-Shalih but with a textual understanding and regardless of the historical context. Some people are not aware that timeis changing, dynamic and developing, but Islam tends to be an exclusive, old-fashioned and not in line with modernity. A textual understanding emerges too much religious believers which had been reproached by previous believers. In fact, the Qur'an has presented testimony in its diction, reminded its people not to be too much, strict and radical. The phenomenon of overpracticing in religion cannot be underestimated, especially in this age of pluralism. Rigidity, and self-righteousness and even labeling other groups having different views as kafir or unbelievers really have negative effects, impacts and consequences. No wonder these dynamics make Moslems dichotomous and splitted, even easily played to fight against each other. This article tries to present how much the effect, impact and bad consequences on the label of kafir on otherMoslems. The researcher hopesto reduce people's carelessness on labelling other Moslems as kafir.